Laki sa hirap - Gatmaitan, Luis P.; Quindoy, David Joel; Chong, Grace (Quezon City LG & M Corporation, 2013)
"Fried chicken for lunch. New school uniforms and shoes. A birthday party with cake and balloons. All these are just dreams for Millet and her siblings. They have to survive daily on the money that their father earns as a tricycle driver. But when tragedy strikes, they are plunged into direr straits than before. Who will come to their rescue? One day, Millet overhears a conversation she should not have, causing her to take matters into her own hands."
Ages 7-13 y.o.
Text in Filipino and English.
Keywords: Children's stories, Philippine (English)